2013
DOI: 10.1186/1476-069x-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of fine particulate matter and asthma reliever dispensations in populations affected by forest fires

Abstract: BackgroundSeveral studies have evaluated the association between forest fire smoke and acute exacerbations of respiratory diseases, but few have examined effects on pharmaceutical dispensations. We examine the associations between daily fine particulate matter (PM2.5) and pharmaceutical dispensations for salbutamol in forest fire-affected and non-fire-affected populations in British Columbia (BC), Canada.MethodsWe estimated PM2.5 exposure for populations in administrative health areas using measurements from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 34 publications
(38 reference statements)
6
75
0
Order By: Relevance
“…One method used to quantify contribution of fire to air quality is to define a circle of a given radius around each PM monitor and assume that all fires within the circle have an effect at the monitoring site (Elliott et al, 2013). However, meteorological conditions such as wind speed and direction also need to be taken into account (Preisler et al, 2005;Preisler et al, 2010;Moeltner, 2013) in order to assess contribution from a particular fire.…”
Section: Introductionmentioning
confidence: 99%
“…One method used to quantify contribution of fire to air quality is to define a circle of a given radius around each PM monitor and assume that all fires within the circle have an effect at the monitoring site (Elliott et al, 2013). However, meteorological conditions such as wind speed and direction also need to be taken into account (Preisler et al, 2005;Preisler et al, 2010;Moeltner, 2013) in order to assess contribution from a particular fire.…”
Section: Introductionmentioning
confidence: 99%
“…Wildfire smoke can be transported over thousands of kilometers, and exposure to wildfire smoke has significant impacts on human health (Künzli et al, 2006;Rappold et al, 2011;Elliott et al, 2013). While US emissions of most major air pollutants are declining (Pinder et al, 2008), increasing fire activity suggests that wildfires may have a greater relative impact on US air quality in the future (Val Martin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to elevated quantities to PM is associated with a more severe detrimental lung function in individuals affected by respiratory diseases. (Pope and Dockery 2006) With regard to wildfire episodes, time series studies performed in several locations obtained an increasing number of hospital admissions due to asthma during wildfire period (Elliott et al 2013;Johnston et al 2002). Vora et al (2011) showed that the 2007 San Diego wildfires may have led to an increase in airways inflammation in asthmatics.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research of wildfire effects was mainly focused on adult mortality and morbidity endpoints (Analitis et al 2012;Caamano-Isorna et al 2011;Crabbe 2012;Delfino et al 2009;Elliott et al 2013;Emmanuel 2000;Hanigan et al 2008;Johnston et al 2007;Vora et al 2011). However, to date, there is still limited research on the impact of wildfire smoke on vulnerable population groups, such as children (Jalaludin et al 2000;Künzli et al 2006;Mirabelli et al 2009).…”
Section: Introductionmentioning
confidence: 97%